Aging Clinical and Experimental Research - Veronese, Nicola; Maggi, Stefania; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Aging Clinical and Experimental Research offers a multidisciplinary forum on the progressing field of gerontology and geriatrics. The areas covered by the journal include: biogerontology, neurosciences, epidemiology, clinical gerontology and geriatric assessment, social, economical and behavioral gerontology. (3z(BAging Clinical and Experimental Research(3y (Bpublishes one volume and one issue each year under Continuous Article Publishing (CAP), and publishes review and research articles, brief reports, perspectives and correspondence, position statements and guidelines. This journal also publishes special/guest edited issues and collections. The peer review process for these articles is the same as the peer review process of the journal in general. Additionally, if the guest editor(s) authors an article in their special issue, they will not handle the peer review process. .s
Keywords: Geriatrics; Geriatrics